Effect in vitro on platelet function of two compounds developed from the pyrimido-pyrimidines - Slater, S. D. (1972)
VK 774 and VK 744, two new compounds developed from the pyrimido-pyrimidines, have been found to be powerful inhibitors of platelet function tested in vitro. They inhibit adenosine diphosphate (ADP)-induced platelet aggregation, and the release of platelet factor 3 by kaolin, and VK 774 also reduces platelet adhesiveness and inhibits platelet aggregation (`snowstorm' effect) in the Chandler tube system. Although measured percentage whole blood clot retraction was uninfluenced by these drugs the clot produced with VK 774 was friable and soft. VK 774 appears to be the most powerful of these compounds reported so far, being active in some test systems at 10(−6)M, and, if the results of toxicity testing are satisfactory, it should be an important agent for therapeutic trial.